Preparing Current and Future Practitioners to Integrate Research in Real Practice Settings. (July 2015) - Thyer, Bruce A.
Past efforts aimed at promoting a better integration between research and practice are reviewed. These include the empirical clinical practice movement (ECP), originating within social work; the empirically supported treatment (EST) initiative of clinical psychology; and the evidence-based practice (EBP) model developed within medicine. The presence of ECP and EST has diminished within the disciplinary literatures, largely replaced by the thriving EBP approach. One serious problem is that EBP is erroneously conflated with the less sophisticated EST model. Apart from embracing EBP, a number of other suggestions are provided to enhance the role of contemporary research in practice decisions. These include strengthening the professional ethical codes relating to clients' rights to effective treatments, insurance policies which preferentially reimburse effective interventions, and ways to encourage practitioners to undertake research themselves or in collaboration with academics. The article concludes by highlighting the significant practice research careers of four exemplary social workers, Gail Steketee, Myrna Weissman, Stephen Wong, and Gerard Hogarty.